Expert knowledge elicitation with SHELF: multiple experts - O'Hagan, Anthony (Henry Stewart Talks, 2023)
SHELF, Mathematical and behavioural aggregation, Group judgements, The rational impartial observer, Eliciting a single distribution from multiple experts, Concept of the rational impartial observer (RIO), Multiple experts in SHELF, SHELF methods, Tertile, quartile, and roulette methods for individual judgements, Probabilities method for group judgements